DEVELOPMENT OF BIOLOGY LEARNING INSTRUCTIONAL TO INCREASE STUDENTS’ ACHIEVEMENT AND SELF-DIRECTED BY SCIENCE PROCESS SKILLS APPROACH - Armansyah Putra; Rudiana Agustini; Yuni Sri Rahayu (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2017)
This research is aimed to develop biology learning materials in Junior High School for plants movement topic to increase students’ achievement and self-directed through Science Process Skill approach. This is development research refers to Kemp’s development model. The learning kit is taught in SMPN 1 Blega Bangkalan Madura for 28 students grade VIII employing science process skill approach. The research design uses One Group Pretest-Posttest and data is analyzed with the qualitative descriptive method. This research reveals that the implementation of learning kit is 83%, dominant student’s activities in 1st and 2nd learning process are observing (22% - 24%), most of the students have positive responses which are indicated by 99% of students expressing their like, the result of students’ learning mastery satisfies the classical criteria for 86%, the rate of students self-directed varies from 55,56% to 83,32%. Based on the data analysis, it can be concluded that the Development of Biology Learning Kit is feasible.Keywords: Achievement, Self-directed, Science Process skill approach.